Inter- and intra-annual variability of potential power production from wave energy converters. (15th February 2019) - Morim, Joao; Cartwright, Nick; Hemer, Mark; Etemad-Shahidi, Amir; Strauss, Darrell
Abstract: Estimation of the variability in the electrical power production and performance over the life-time of wave energy converters (WEC) is paramount for the economic viability of potential wave farm projects. In this research, the significance of the inter-annual variability in the potential production performance (PPP) is demonstrated, using power conversion matrices of ten pre-commercial WEC devices and an existing 31-year wave hindcast case study from the central shelf of New South Wales, Australia. The variability in the PPP over the intra- and inter-annual time scales is found to be comparable, hence indicating that making predictions merely based on annual and monthly averages could be misleading and that inter-annual fluctuations should be considered in future analysis. The results also show that inter-annual variations in WEC production performance can be significantly higher than that of the wave energy resource (WER) owing to the efficiency of different WECs relative to the local sea state conditions. We also demonstrate that optimization of WEC performance for the local sea state cannot only potentially lead to improved power yields but also a decrease in the intra- and inter-annual variability in PPP.